2021
DOI: 10.1093/ndt/gfab031
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of the nuclear factor erythroid 2-related factor 2 (NRF2) system in human chronic kidney disease: alterations, interventions and relation to morbidity

Abstract: Background NRF2 and its effectors NAD(P)H:quinoneoxidoreductase 1 (NQO1) and heme oxygenase 1 (HO-1) are of interest in kidney disease. We therefore reviewed studies about their status in patients with chronic kidney disease (CKD). Methods We undertook systematic searches of PubMed and EMBASE databases. Alterations of NRF2, NQO1 and HO-1 in CKD, their responses to interventions and their relation to clinically relevant parame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 108 publications
(217 reference statements)
0
18
0
Order By: Relevance
“…[88][89][90][91] A recent systematic review of 32 studies concludes that whereas Nrf2 expression was consistently downregulated in CKD, NQO1, and HO-1 showed varying alterations related to inflammation, comorbidities, and severity of kidney damage. 92 Jiang et al 69 showed that kidney biopsy specimens from patients with DKD demonstrated high levels of glucose-induced ROS in mesangial cells as well as activation of Nrf2 and downstream genes. By immunohistochemistry, it was demonstrated that whereas Nrf2 was expressed at low levels in normal glomeruli, it was up-regulated in glomeruli from patients with DKD.…”
Section: Proinflammatory Mediators In Ckdmentioning
confidence: 99%
“…[88][89][90][91] A recent systematic review of 32 studies concludes that whereas Nrf2 expression was consistently downregulated in CKD, NQO1, and HO-1 showed varying alterations related to inflammation, comorbidities, and severity of kidney damage. 92 Jiang et al 69 showed that kidney biopsy specimens from patients with DKD demonstrated high levels of glucose-induced ROS in mesangial cells as well as activation of Nrf2 and downstream genes. By immunohistochemistry, it was demonstrated that whereas Nrf2 was expressed at low levels in normal glomeruli, it was up-regulated in glomeruli from patients with DKD.…”
Section: Proinflammatory Mediators In Ckdmentioning
confidence: 99%
“…At indoxyl-sulfate concentrations between 1 mg/L and 11 mg/L in patients with CKD3 and 4, indoxyl sulfate correlated positively with Nrf2 gene expression in peripheral blood polymorphonuclear cells (PBMCs) [ 121 ]. In light of a mainly decreased Nrf2 gene expression in advanced CKD [ 122 ], a bi-phasic, concentration-dependent effect of indoxyl sulfate in human CKD seems plausible, with Nrf2 activation in the lower concentration range and Nrf2 repression at high concentrations.…”
Section: Clinical Data Of Nrf2 Activation In Human Ckdmentioning
confidence: 99%
“…Herein, in patients with CKD3/4, higher NF-κB gene expression was associated with higher Nrf2 gene expression, likely reflecting NF-κB-driven pro-inflammatory responses and subsequent Nrf2 activation. On the other hand, in the patient group with CKD5 and hemodialysis therapy, the decrease in Nrf2, which has frequently been observed in advanced CKD [ 122 ], was present. In this group, decreased Nrf2 gene expression was associated with significantly increased NF-κB, finally amounting to a doubling of NF-κB gene expression [ 131 ] that may reflect a lack of suppressive Nrf2 action on NF-κB.…”
Section: Clinical Data Of Nrf2 Activation In Human Ckdmentioning
confidence: 99%
“…As in other areas of complex regulations in kidney disease, the combined investigation of a set of meaningful molecular parameters is inevitable. Thorough analyses of gene expression, protein characteristics, and protein activity together enable a better understanding of molecular networks [ 128 ]. Ideally, in investigations of inflammasomes, this comprises the gene expression and protein amount of inflammasome-related components, post-translational modifications of the inflammasome sensory components, inflammasome assembly and proteolytic activity, and production of mature interleukins [ 11 ].…”
Section: Inflammasome Components In Akimentioning
confidence: 99%